Exploring the knowledge and awareness on applications of virtual reality and augmented reality technology among dental healthcare professionals – a crosssectional survey - Zahra Masood; Hafsa Qabool; Mubassar Fida; Rashna Hoshang Sukhia; Mubassar Fida (Journal of the Pakistan Medical Association, 2024)
Objective: To assess the knowledge and awareness of Virtual Reality (VR) and Augmented Reality (AR) technologyin dentistry. Methods: A questionnaire survey-based study was conducted using Google forms on a sample of 273 dentalhealthcare professionals (DHCP) from October- November 2023, after obtaining ethical approval. A validatedquestionnaire, divided into three sections, was used to assess the knowledge and awareness of dental healthcareprofessionals on virtual and augmented reality. Section A was about demographic statistics, section B assessedknowledge and awareness regarding VR and AR and section C consisted of future acceptability of VR and AR amongDHCP. The frequency of each question was reported in percentages. To assess the difference of knowledge andawareness of AR and VR among different specialties of DHCP, one-way ANOVA test was applied and in case ofsignificant results pairwise comparison was performed by post-hoc Tukey test. Results: There was a statistically significant difference of knowledge (1.40 ± 0.49) among different dental healthcareprofessionals. On pairwise comparison, a statistically significant difference (p = <0.05) of knowledge and awarenessof AR and VR was found among dental specialist and other dental health professionals. Conclusions: A concerning lack of knowledge and awareness among dental healthcare professionals regarding ARand VR technology in dentistry was found. Interestingly, within the spectrum of specialties, dental specialistsdemonstrated a comparatively higher awareness than their counterparts in other specialties. Addressing barriers,notably a lack of knowledge, is crucial for successful technology adoption in dental education and practice. Keywords: Augmented Reality, Virtual Reality, Dentistry, Education, Demography, Health Care, Variance,Technological Integration.